Kajian Bentuk dan Makna Pengantin Kebesaran Menak Sopal Trenggalek Jawa Timur - Amarisyah, Sabrina Nadhifa; Nia Kusstianti; Biyan Yesi Wilujeng; Mutimmatul Faidah (Jurnal Tata Rias, 2026)
Menak Sopal Bridal Makeup is one of the traditional bridal makeup styless from Trenggalek Regency. This Bridal style remains relatively unknown to the wider public due to the lack of exploration, publication and academic literature. This study aims to describe the form and meaning of the makeup, hair styling, attire and accessories used in Menak Sopal Bridal Makeup. The Method used is qualitative descriptive, with data collected through interviews, observations and documentation, applying triangulation of sources, methods, and theories. The results show that the makeup used is form of beautiful makeup that highlights feminine elegance. The hair styling and accesories symbolize prosperity, armony, as well as prayers and blessing in married life. The attire reflects the richness of marine life, representing balance, hope, and the roles of husband and wife in household. The accsesories meanings of strength and protection. All of these elements represent harmony between nature and humans, spiritual values, and pride in the natural wealth of Trenggalek Regency